1999
DOI: 10.1016/s1010-7940(99)00005-6
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary shunt prevents left ventricular function impairment during beating heart coronary revascularization1

Abstract: (i) occlusion of the LAD to perform the anastomosis results in temporary impairment in left ventricular function with complete recovery on reperfusion; (ii) the use of an intracoronary shunt presumably by maintaining myocardial perfusion prevents deterioration in ventricular function; (iii) from this data it seems therefore advisable to use an intracoronary shunt in patients with unstable angina, poor left ventricular function, or in cases in which a longer time to perform the anastomosis is anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 19 publications
1
33
1
2
Order By: Relevance
“…Prevention of ventricular function and avoiding myocardial injury seem to be possible with the use of TICS [4,5]. TICS had been used in OPCAB since 1975.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of ventricular function and avoiding myocardial injury seem to be possible with the use of TICS [4,5]. TICS had been used in OPCAB since 1975.…”
Section: Introductionmentioning
confidence: 99%
“…This system has the double advantage of drying the anastomotic site (hemostatic effect) while allowing an effective distal coronary perfusion (myocardial protection), which may sometimes be necessary in OPCAB surgery [15]. Lucchetti et al [16] reported that intracoronary shunts are beneficial during OPCAB in patients with isolated left anterior descending (LAD) coronary artery lesion. They showed that intracoronary shunts prevented impairment in left ventricular function during construction of coronary anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary shunts are inserted into the native coronary artery during construction of the anastomoses; this is thought to improve distal perfusion and thereby reduce local ischemia during surgery. 16,17 Cardiovascular magnetic resonance imaging (CMR) is accepted as the gold standard for the assessment of biventricular function. 18 The technique allows serial cardiac assessment with excellent reproducibility, permitting a significant sample size reduction for heart failure trials.…”
Section: Clinical Perspective P 2138mentioning
confidence: 99%
“…The present study suggests that the combination of bypass and intracoronary shunts may still not be adequate to perfuse the distal coronary territories, especially in the presence of significant proximal coronary disease. Furthermore, although 2 studies using intracoronary shunts have demonstrated improved intraoperative regional and global cardiac function during the insertion of a shunt, 16,17 both studies examined only the short-term effect. Actual shunt insertion may cause endothelial trauma or plaque disruption in the native vessel, producing embolization of material and possible downstream myocardial injury.…”
Section: Irreversible Myocardial Injurymentioning
confidence: 99%
See 1 more Smart Citation